2001
DOI: 10.1042/0264-6021:3560805
|View full text |Cite
|
Sign up to set email alerts
|

Response of neurons to an irreversible inhibition of endoplasmic reticulum Ca2+-ATPase: relationship between global protein synthesis and expression and translation of individual genes

Abstract: In the physiological state, there appears to be a regulatory link between endoplasmic reticulum (ER) Ca(2+) homoeostasis and the initiation of neuronal protein synthesis. Exposing neuronal cell cultures to thapsigargin (Tg), an irreversible inhibitor of sarcoplasmic/ER Ca(2+)-ATPase (SERCA), induced an almost complete suppression of protein synthesis, which recovered to approx. 60% of control 24 h after Tg exposure. This is an experimental model where the regulatory link between the initiation of protein synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 45 publications
(22 reference statements)
1
37
0
Order By: Relevance
“…Recently, we confirmed that our primary neuronal cell cultures react to ER stress with an activation of the unfolded protein response (UPR), a severe suppression of the initiation step of protein synthesis and a 100-to 200-fold increase in mRNA levels of genes coding for ER stress proteins, including grp78, grp94, and gadd153 (28). In contrast, the expression of genes such as hsp70, which do not react specifically to ER stress, were only slightly activated (28). We found their degree of activation to be similar to that of parkin.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Recently, we confirmed that our primary neuronal cell cultures react to ER stress with an activation of the unfolded protein response (UPR), a severe suppression of the initiation step of protein synthesis and a 100-to 200-fold increase in mRNA levels of genes coding for ER stress proteins, including grp78, grp94, and gadd153 (28). In contrast, the expression of genes such as hsp70, which do not react specifically to ER stress, were only slightly activated (28). We found their degree of activation to be similar to that of parkin.…”
Section: Resultsmentioning
confidence: 64%
“…Besides the moderate increase in neuronal parkin mRNA levels observed in cultures exposed to ER stress, activation of the translation of parkin may be hindered and the extent of this effect is related to the level of suppression of global protein synthesis under our experimental conditions (28). Evidence is indeed accumulating to suggest that the normal stress response of cells is suppressed in neurons.…”
Section: Resultsmentioning
confidence: 99%
“…GRP78 was present in nontreated control cells and increased in response to treatment with thapsigargin (an inhibitor of sarco ER Ca 2 þ ATPase and a representative inducer of the ER stress response), as previously described. 19 Indomethacin slightly but significantly increased the amount of GRP78 (Figure 2). We also examined the effect of indomethacin on the expression of another ER stress response-related protein, CHOP, a transcription factor, which induces apoptosis.…”
Section: Induction Of Grp78 and Chop By Indomethacin Associated With mentioning
confidence: 94%
“…CHOP was not present in nontreated cells, but was induced by thapsigargin, this being consistent with previously reported results. 19 Indomethacin clearly induced CHOP, and to a greater extent than thapsigargin ( Figure 2). …”
Section: Induction Of Grp78 and Chop By Indomethacin Associated With mentioning
confidence: 94%
“…Likewise, persistent blockade of protein synthesis is associated with brain damage (10), and neuronal survival after focal ischemia may depend on the recovery of protein synthesis (11). Intracellular Ca 2ϩ overload by activation of glutamate receptors (12) or disturbances of endoplasmic reticulum Ca 2ϩ homeostasis decrease protein synthesis (13)(14)(15)(16). Protein synthesis is mainly regulated at the initiation step.…”
mentioning
confidence: 99%